Comparison between six varieties of drought-tolerant rice in three selected countries: a review / Fatheen Nurasheqeen Faizul Maiza - Faizul Maiza, Fatheen Nurasheqeen (Faculty of Plantation and Agrotechnology, 2018)
Rice (Oryza sativa L.) is one of the most significant crops for man consumption. The purpose of the study is to review the characteristic of drought-tolerant rice varieties in three different countries; India, Bangladesh, and Malaysia. These countries are the main producer of rice and at the same time are facing with water stress condition. For each country, two varieties that are tolerant to drought were discussed. The varieties that were chosen for this review are Sahbhagi Dhan and Vandana form India, BRRI Dhan 56 and BRRI Dhan 57 from Bangladesh and MR219 and MR220 from Malaysia. Drought can be devastating to a farmer’s harvest as the plants are starved of essential water resources. Drought stress can happen at any growth level. Severe droughts will threaten farmers’ ability to provide a steady food supply. Therefore, many rice-producing countries are focusing on the production of suitable rice variety which can thrive during drought condition. Most of the drought-tolerant varieties showed early maturation between 90 to 120 days and are deep-rooted. With more often occurrence of drought in rainfed rice ecosystems, it is necessary to enhance the adoption of drought tolerant varieties to sustain both household food and income, security as these varieties fetch higher income to the farmers and withstand water stress and guaranteeing the farmers the required yield to sustaining a livelihood. From the review, rice variety that was developed in Malaysia showed the most promising characteristics as the production can reach more than 10 tonnes per hectare as compared to other countries. As a conclusion, each of the variety possesses its own characteristic and were developed through different methods.